2016
DOI: 10.1186/s13008-016-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma-induced apoptosis of head and neck squamous cell carcinoma is connected to indoleamine-2,3-dioxygenase via mitochondrial and ER stress-associated pathways

Abstract: BackgroundTumor response to immunotherapy is the consequence of a concerted crosstalk between cytokines and effector cells. Interferon gamma (IFNγ) is one of the common cytokines coordinating tumor immune response and the associated biological consequences. Although the role of IFNγ in the modulation of tumor immunity has been widely documented, the mechanisms regulating IFNγ-induced cell death, during the course of immune therapy, is not described in detail.ResultsIFNγ triggered apoptosis of CLS-354 and RPMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…The main focus of our present study was therefore to further delineate the morphologic phenotype of the immunologic tumor-host interaction in OSCC as described in the cancer immunity cycle (15,20), in particular to exactly describe the composition of the inflammatory infiltrate involved in cell-mediated immunity, composed by various subsets of T cells (CD3 + T cells; CD4 + T cells; CD8 + T killer cells; CD4 + FOXP3 + Tregs; IL-17A + Th17 cells) and its association with HLA class I expression, IFN-g expression, and morphology, taking into account spatial heterogeneity of immunologic parameters (stroma versus epithelial infiltrate; IF versus TCe). As previously described, the immune cell infiltrate as well as HLA class I and IFN-g play an important role in head and neck squamous cell carcinoma (26,27,36,38,51,52). Confirming these findings, we found a strong positive association of high intraepithelial and stromal CD3 + , CD4 + , CD8 + , CD4 + FOXP3 + , and IL-17A + inflammatory infiltrate not only with each other but also with high HLA class I and presence of IFN-g expression in TILs.…”
Section: Discussionmentioning
confidence: 78%
“…The main focus of our present study was therefore to further delineate the morphologic phenotype of the immunologic tumor-host interaction in OSCC as described in the cancer immunity cycle (15,20), in particular to exactly describe the composition of the inflammatory infiltrate involved in cell-mediated immunity, composed by various subsets of T cells (CD3 + T cells; CD4 + T cells; CD8 + T killer cells; CD4 + FOXP3 + Tregs; IL-17A + Th17 cells) and its association with HLA class I expression, IFN-g expression, and morphology, taking into account spatial heterogeneity of immunologic parameters (stroma versus epithelial infiltrate; IF versus TCe). As previously described, the immune cell infiltrate as well as HLA class I and IFN-g play an important role in head and neck squamous cell carcinoma (26,27,36,38,51,52). Confirming these findings, we found a strong positive association of high intraepithelial and stromal CD3 + , CD4 + , CD8 + , CD4 + FOXP3 + , and IL-17A + inflammatory infiltrate not only with each other but also with high HLA class I and presence of IFN-g expression in TILs.…”
Section: Discussionmentioning
confidence: 78%
“…PD‐1 and CTLA‐4 are the most studied checkpoint target molecules, and PD‐L1 expression is reported as a predictive biomarker in cancer immunotherapy . LAG‐3 and TIM3 are the next promising inhibitory checkpoints to be translated to the clinic, are highly expressed on exhausted or dysfunctional T cells in infection and cancer . Blockade of IDO‐1 combined with checkpoint receptors has been found to induce prominent antitumor responses in various solid tumors .…”
Section: Discussionmentioning
confidence: 99%
“…18 LAG-3 and TIM3 are the next promising inhibitory checkpoints to be translated to the clinic, are highly expressed on exhausted or dysfunctional T cells in infection and cancer. 19,20 Blockade of IDO-1 combined with checkpoint receptors has been found to induce prominent antitumor responses in various solid tumors. 21 Previous study has reported that PD-1 + and TIM-3 + tumorinfiltrating lymphocytes were increased after cetuximab therapy in HNSCC patients, and the increased frequency of PD-1 + and TIM-3 + TILs was inversely correlated with clinical outcome of cetuximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor response to immunotherapy is a consequence of a concerted crosstalk between cytokines and effector cells . IFN‐γ is one of the central cytokines that coordinates tumor immune responses and the associated biological consequences and shows antitumor activity combined with IDO in patients with non‐small‐cell lung carcinoma and in HNSCC cell lines . The PD‐1:PD‐L1/PD‐L2 pathway has been implicated in tumor escape from immune destruction in various cancers .…”
Section: Discussionmentioning
confidence: 99%